DIGNITY OF LIFE AND PERSON-CENTRED PROCESSES FOR ADVANCE CARE PLANNING IN THE COMMUNITY. Issue 2 (1st June 2013) - Smith, C; Jaffray, L; Ellis, I
Abstract : Background: As life expectancy increases, so do the number of elderly people living with advanced life-limiting chronic illness, including prolonging life through artificial or mechanical means. The aim of Advance Care Plans is to ensure that individual's treatment wishes and preferences are known and respected. Aim: Whilst research continues in regard to the development of electronic Advance Care Plans in the palliative care setting and residential aged care setting, there is a need to understand the relevance and practicality of developing Advance Care Plans for use by elderly people living with life-limiting chronic illnesses in the community. Methods: Systematic review—models of Advance Care Planning for elderly people living in the community Meta- analysis and meta-synthesis Interviews—sample of ACP programme stakeholders and community dwelling elderly (early 2013) Results: Seventy-one papers resulted from the search strategy with 17 papers selected for review. A meta-analysis and meta-synthesis has informed our proposed model for electronic Advance Care planning in the community—the Dignity of Life Model (a person-centred and dignity of life focussed approach). Interview data will inform the relevance and practicality of this proposed model. Discussion: This research will assist to understand the relevance and practicality of developing an electronic Advance Care Plan (eAPC) for use by elderly people living with life-limiting chronic illnesses in the community. Conclusion: Provide guidance on a model for electronic Advance Care Plan (eAPC) for use by elderly people living with life-limiting chronic illnesses in the community.